2018
DOI: 10.3389/fneur.2018.00471
|View full text |Cite
|
Sign up to set email alerts
|

Next-Generation Sequencing of Cerebrospinal Fluid for the Diagnosis of Neurocysticercosis

Abstract: Background: Neurocysticercosis (NCC) is the most common helminthic infection of the central nervous system (CNS). The diagnosis of NCC is sometimes challenging due to its heterogenous clinical manifestations and the variable sensitivity and specificity of neuroimaging and serological tests.Methods: Next-generation sequencing (NGS) of cerebrospinal fluid (CSF) was used to detect pathogens in patients with clinically suspected CNS infections. A series of patients diagnosed with NCC is reviewed here.Results: Usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 19 publications
4
24
0
Order By: Relevance
“…Importantly, mNGS can detect unsuspected pathogens that clinicians may fail to consider because of atypical clinical manifestations. Many cases of neurological infections have been unexpectedly diagnosed by mNGS of CSF 11,22,29,30 similar to the present study for the cases of L. monocytogenes , Brucella and T. solium 1214 . In addition, as demonstrated in previous studies 10,20,21 and in the present study for the case of encephalitis caused by Suid herpesvirus 1 31 , mNGS of CSF has the ability to identify novel aetiologies of CNS infections.…”
Section: Discussionsupporting
confidence: 87%
“…Importantly, mNGS can detect unsuspected pathogens that clinicians may fail to consider because of atypical clinical manifestations. Many cases of neurological infections have been unexpectedly diagnosed by mNGS of CSF 11,22,29,30 similar to the present study for the cases of L. monocytogenes , Brucella and T. solium 1214 . In addition, as demonstrated in previous studies 10,20,21 and in the present study for the case of encephalitis caused by Suid herpesvirus 1 31 , mNGS of CSF has the ability to identify novel aetiologies of CNS infections.…”
Section: Discussionsupporting
confidence: 87%
“…Importantly, mNGS can detect unsuspected pathogens that clinicians may fail to consider because of atypical clinical manifestations. Many cases of neurological infections have been unexpectedly diagnosed by mNGS of CSF [11,22,29,30] similar to the present study for the cases of L. monocytogenes, Brucella and T. solium [12][13][14]. In addition, as demonstrated in previous studies [10,20,21] and in the present study for the case of encephalitis caused by Suid herpesvirus 1 [31], mNGS of CSF has the ability to identify novel aetiologies of CNS infections.…”
Section: Discussionsupporting
confidence: 89%
“…Compared with traditional individual target-specific tests, mNGS can identify pathogens without the input of clinical predictors or prior laboratory results. Several recent studies have demonstrated the capability of mNGS of CSF to identify known and unsuspected pathogens and to discover new microorganisms [10][11][12][13][14][15][16][17][18]. mNGS of CSF is being increasingly utilized in routine clinical settings for the rapid diagnosis of central nervous system infections.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This case thus highlights the utility of mNGS for the diagnosis of atypical presentations of common infections. 24,68,69 The case also vividly illustrates that either improvement or lack of clinical deterioration in the setting of immunosuppression does not rule out an underlying infectious etiology, even after years of treatment.…”
Section: Follow-upmentioning
confidence: 99%